2015
DOI: 10.1186/s12936-015-0659-6
|View full text |Cite
|
Sign up to set email alerts
|

Factors impeding the acceptability and use of malaria preventive measures: implications for malaria elimination in eastern Rwanda

Abstract: BackgroundLong-lasting insecticidal nets (LLIN), indoor residual spraying (IRS) and malaria case treatment with artemisinin-based combination therapy (ACT) have been proven to significantly reduce malaria, but may not necessarily lead to malaria elimination. This study explored factors hindering the acceptability and use of available malaria preventive measures to better inform area specific strategies that can lead to malaria elimination.MethodsNine focus group discussions (FGD) covering a cross-section of 81… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
69
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(77 citation statements)
references
References 22 publications
8
69
0
Order By: Relevance
“…However, bedbug infestation of LLINs and perceptions that IRS activated mosquitos, rather than killing them were enumerated as hindrances for use in a series of focus group discussions [20]. Furthermore, only two-thirds of the population was found to have a community based health insurance (CBHI) at baseline while malariometric data showed a 5% malaria parasite carriage prevalence (asymptomatic) and 13% of households had at least one member with malaria parasitemia [20, 21]. …”
Section: Resultsmentioning
confidence: 99%
“…However, bedbug infestation of LLINs and perceptions that IRS activated mosquitos, rather than killing them were enumerated as hindrances for use in a series of focus group discussions [20]. Furthermore, only two-thirds of the population was found to have a community based health insurance (CBHI) at baseline while malariometric data showed a 5% malaria parasite carriage prevalence (asymptomatic) and 13% of households had at least one member with malaria parasitemia [20, 21]. …”
Section: Resultsmentioning
confidence: 99%
“…Some household participants expressed their worry about the possibility of having the contents of their belongings revealed to the public by some unscrupulous spray operators. A similar study in Tanzania reported that the fear of domestic intrusion led to the perception that spray operators were spying on people's lives [55], while a similar concern in Rwanda resulted in some householders refusal to spray their bedrooms and storage areas [63]. In a sociological analysis of the impact of vector control at the household level, some scholars argued that the entry into homes by uniformed male spray operators not only extends the power of public institutions into the domestic front, but also raises serious security concerns since the householders present during the day-when spraying is conducted-are mostly women and children [64].…”
Section: Discussionmentioning
confidence: 99%
“…The absence of nets most frequently in a household is probably predisposing the family members, especially susceptible groups to malaria. Although a study mentioned that bedbug jeopardize persistent net utilization or barrier to net users [3][4][5]12], another study that focused on Bedbug containment practices [9,13], no detailed evidence available on the magnitude of the Bedbug versus net utilization.…”
Section: Discussionmentioning
confidence: 99%
“…Possibly, this bene t is believed to play a vital role in improving community acceptance of LLINs for malaria vector control [11]. Nevertheless, the lethal dose to mosquito vectors appears not only ineffective to kill bedbugs and managed to reproduce and multiplied rapidly on nets [12,13], but also irritates them to come out of their hide and actively feed on human. Although the resurgence of bedbug is documented, the reason why rises in resurgence of bedbugs infestations not yet well understood [14,15].…”
Section: Introductionmentioning
confidence: 99%